Comparable long term psychosocial burden in patients with lower grade versus higher grade brain tumors - Simone D’Souza; Stefanie Fuchs; Marco Skardelly; Stephan Zipfel; Björn Falkenburger; Martin Teufel (Scientific Reports)
Abstract Patients with higher grade brain tumors (PwHG) frequently experience anxiety and depression, while patients with lower grade brain tumors (PwLG) may also develop these issues over time. However, it remains unclear whether PwLG face additional psychosocial challenges, such as reduced hope, heightened distress, or impaired coping, compared to PwHG. This study aimed to comparatively analyze hope, distress, coping, anxiety, and depression in PwLG versus PwHG to inform psychosocial screening and care. A total of 66 patients were assessed using the Distress Thermometer (DT), Generalized Anxiety Disorder questionnaire-2 (GAD-2), Patient Health Questionnaire-2 (PHQ-2), Herth Hope Index (HHI), and a self-developed coping questionnaire across three time points. Repeated-measures ANOVAs, post-hoc Bonferroni tests, and Friedman tests were conducted. Results revealed no significant group differences in distress, anxiety, or depression. PwLG exhibited a decline in hope (p = 0.044) and treatment success expectations (p = 0.018) over time, mirroring patterns observed in PwHG. These findings indicate that PwLG and PwHG face comparable psychosocial burdens, suggesting that similar psychosocial interventions may benefit both groups.